Structure D'un Réseau Electrique Intelligent Avec L'intégration D'énergies Renouvelable - Baha, Mortadha; Meftah ,Mohamed El Had (University of El-Oued, 2022)
"The development of such an energy system, must guarantee the security, stability, and reliability as well as the quality of energy, therefore there are two important elements which must be present are the renewable energies in a so-called hybrid system at the production level and an intelligent network at the management level. Our study is interested in giving a general definition of an intelligent network and its operating principle by presenting the different active elements that distinguish it from the conventional network. On the other hand, there is also a non-traditional consumer. It is the electric vehicle which becomes a very important element in the new electrical system, because the imbalance that it causes to the network during the recharging operation. This is why we will carry out on the MATLAB environment a simulation for the integration of each renewable energy source with a non-renewable source. Assuming diesel. Thereafter we will simulate and study a hybrid system consisting of a photovoltaic source, wind and a diesel source (conventional). Which powers a load containing the electric car" "كل تطور لنظام طاقوي ما يجب أن يضمن السالمة واالستقرار والموثوقية باإلضافة إلى جودة الطاقة، لذلك سيكون من المهم حضور عنصران مهمان وهما الطاقات المتجددة على مستوى محطات التوليد فيما يسمى بالنظام الهجين وشبكة ذكية على مستوى التسيير واإلدارة . تهتم دراستنا بإعطاء تعريف عام للشبكة الذكية ومبدأ عملها من خالل تقديم مختلف العناصر النشطة التي تميزها عن الشبكة التقليدية. من جهة أخرى ومن ناحية المستهلك هناك أي ًضا مستهلك غير تقليدي. يدعى بالسيارة الكهربائية. اذ انها تمثل عنص ًرا مهًما جدًا في النظام الكهربائي الجديد، بسبب الخلل الذي تخلفه في الشبكة أثناء عملية إعادة الشحن. لهذا السبب سنجري محاكاة على بيئة MATLAB تتمثل في دمج بعض من مصادر الطاقة المتجددة مع مصدر غير متجدد. بافتراض الديزال . بعد ذلك سنقوم بمحاكاة ودراسة نظام هجين يتكون من مصدر ضوئي ورياح وديزل )تقليدي(. الذي يغذي حمولة تحتوي على السيارات"
مذكرات ماستر تخصص شبكات
Keywords: Renewable énergy; hybrid systeme; véhicule electrique; photovoltaic; smart grid; Converter; الطاقة المتجددة، النظام الهجين، السيارة الكهربائية، الطاقة الشمسية الضوئية، الشبكة الذكية، المحول